Development and Psychometric Characteristics of the TBI-QOL Communication Item Bank. Issue 5 (September 2019) - Cohen, Matthew L.; Kisala, Pamela A.; Boulton, Aaron J.; Carlozzi, Noelle E.; Cook, Christine V.; Tulsky, David S.
Abstract : Objective: To develop an item response theory (IRT)-based patient-reported outcome measure of functional communication for adults with traumatic brain injury (TBI). Setting: Five medical centers that were TBI Model Systems sites. Participants: A total of 569 adults with TBI (28% complicated-mild; 13% moderate; and 58% severe). Design: Grounded theory-based qualitative item development, large-scale item calibration testing, confirmatory factor analyses, psychometric analyses with graded response model IRT. Main Measure: Traumatic Brain Injury-Quality of Life (TBI-QOL) Communication Item Bank, version 1.0. Results: From an initial pool of 48 items, 31 items were retained in the final instrument based on adequate fit to a unidimensional model and absence of bias across several demographic and clinical subgroupings. The TBI-QOL Communication Item Bank demonstrated excellent score precision (reliability ≥ 0.95) across a wide range of communication impairment levels, particularly for individuals with more severe difficulties. The TBI-QOL Communication Item Bank is available as a full item bank, fixed-length short form, and as a computerized adaptive test. Conclusions: The TBI-QOL Communication Item Bank permits precise measurement of patient-reported functional communication after TBI. Future development will validate the instrument against performance-based, clinician-reported, and surrogate-reported assessments.